2017
DOI: 10.1021/acs.langmuir.7b02047
|View full text |Cite
|
Sign up to set email alerts
|

Mustard Gas Surrogate Interactions with Modified Porous Carbon Fabrics: Effect of Oxidative Treatment

Abstract: Removal of chemical warfare agent (CWA) surrogates by highly porous carbon textiles was investigated. The carbon cloth was modified by oxidation in a mixture of concentrated sulfuric and nitric acid. This process did not affect textile structural integrity. The surface properties of the modified textiles were investigated, and their capabilities to remove 2-chloroethyl ethyl sulfide (CEES) and diethylsulfide (EES), two mustard gas surrogates, were evaluated. The oxidized carbon textiles have a highly active su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 60 publications
(84 reference statements)
1
25
0
Order By: Relevance
“…Great effort has been given to achieve higher porosity, predominately by increasing the size of the linkers, leading to significantly higher structural feature values when compared to commonly used activated carbons and zeolites [42][43][44][45][46]. A characteristic example is Cu 3 (BHEHPI) or NU-110 (NU stands for Northwestern University in Chicago, USA), which has the highest reported surface area and total pore volume up to now [34,44].…”
Section: Metal Organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Great effort has been given to achieve higher porosity, predominately by increasing the size of the linkers, leading to significantly higher structural feature values when compared to commonly used activated carbons and zeolites [42][43][44][45][46]. A characteristic example is Cu 3 (BHEHPI) or NU-110 (NU stands for Northwestern University in Chicago, USA), which has the highest reported surface area and total pore volume up to now [34,44].…”
Section: Metal Organic Frameworkmentioning
confidence: 99%
“…The reason behind this instability is the ability of water to interact with the metal ions/clusters competitively to the linkers, leading to the collapse of the framework. There are also various other factors that play a crucial role in the stability of the MOFs, with the most important being crystallinity, hydrophobicity, and the extent of the defectous sites [43]. Additionally, the temperature and pH should also be considered.…”
Section: Metal Organic Frameworkmentioning
confidence: 99%
“…M. Florent et al [96] (2017) reported an investigation on removal of chemical warfare agent (CWA) surrogates by highly porous carbon textiles. The surface morphology of modified carbon cloths was studied and found that the modified materials has capabilities to remove 2-chloroethyl ethyl sulfide (CEES) and diethyl sulfide (EES), two sulfur mustard gas simulants.…”
Section: Literature Surveymentioning
confidence: 99%
“… 19 , 22 , 23 Highly oxidized porous carbon surfaces have shown to decompose simulants for HD up to 80% decomposition after 24 h of contact with the oxidized carbon surfaces. 24 While these methods address the need for providing improved protection for individuals who encounter CWAs, they have limited application for large-scale degradation of agents, which are typically addressed through chemical treatment. 25 Of these methods, hydrolysis and oxidation are among the most common methods currently used to decompose chemical agents.…”
Section: Introductionmentioning
confidence: 99%